Peningkatan Pengetahuan Peternak Sapi Potong terhadap Teknologi Pengolahan Jerami Padi di Kabupaten Seluma - Robiyanto Robiyanto; Harwi Kusnadi; Yesmawati Yesmawati (Seminar Nasional Lahan Suboptimal, 2018)
Robiyanto et al, 2019. Increased Knowledge of Beef Cattle Farmers on Rice straw Processing Technology in Seluma District. pp. 488-494.The role of counseling in building farmers 'awareness and socializing rice straw processing technology is very important to encourage farmers' knowledge about processing rice straw. This study aimed to determine the increase of farmers' knowledge about processing rice straw as beef cattle feed. This research was conducted in Rimbo Kedui Sub-district, South Seluma District, Seluma Regency, Bengkulu Province during the socialization of rice straw processing in the Bioindustry of cattle rice activities. The number of respondents as many as 15 people to measure the level of knowledge of breeders consisting of the questionnaire pre test and post test. From the results of the implementation of the pre test and post test. obtained the highest increase in breeders' knowledge by 37.16% from 23.33 to 32.00. The results of evaluating the level of knowledge of breeders based on the highest level of knowledge improvement education at the junior high school education level of 58.82% from 33.75 to 21.25. The increase in knowledge based on age groups, the highest increase in knowledge aged 41 - 50 years was 44.44% from 22.50 to 32.50. Increased knowledge based on business duration increased the highest knowledge by 44.44% from 22.50 to 32.50 business times 21-30 years.